2020
DOI: 10.1186/s12891-020-03400-4
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-based quantification of fatty degeneration in the supraspinatus muscle on MRI as an alternative method to Goutallier classification and single-voxel MR spectroscopy

Abstract: Background: Conventional fat quantification methods for rotator cuff muscles have various limitations, such as inconsistent reliabilities of the Goutallier grades and need for advanced techniques in quantitative MRI sequences. We aimed to examine a threshold-based fat quantification method in the supraspinatus muscle on standard T1weighted MR images and compare the threshold-based method with Goutallier grades and MR spectroscopy. Methods: We retrospectively examined 38 symptomatic patients, who underwent T1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Fatty infiltration in the RC muscles is highly related to the retear rate and shoulder function postoperatively, which was evaluated several decades ago in clinical settings. 32,33,47,48 With advances in imaging techniques, intramuscular FF can be fully captured through 3D models, with theoretically high reliability and strong objectivity. 54 Several studies recently compared 2D-FF from traditional single sagittal slices and 3D-FF measured by modified 3D methods to determine their differences in clinical scenarios; however, the conclusions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty infiltration in the RC muscles is highly related to the retear rate and shoulder function postoperatively, which was evaluated several decades ago in clinical settings. 32,33,47,48 With advances in imaging techniques, intramuscular FF can be fully captured through 3D models, with theoretically high reliability and strong objectivity. 54 Several studies recently compared 2D-FF from traditional single sagittal slices and 3D-FF measured by modified 3D methods to determine their differences in clinical scenarios; however, the conclusions were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Atrophic changes and fatty infiltration of the rotator-cuff musculature are two of the more commonly accepted findings associated with large tears, and several methods for quantifying these changes have been described 12 , 14 , 15 . The scapular Y-view of the MRI, the lateral-most T1 sagittal MR image in which the scapular spine and body are in contact, is the base image for obtaining reliable indicators of the supraspinatus muscle status (for example, occupation ratio, tangent sign, and fatty infiltration) 14 , 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…If the intensity distribution in the image is clear, a more accurate classification is possible. Therefore, Otsu thresholding is expected to easily detect a threshold value at the pixel intensity, which maximizes the differences between the foreground (bright) and background (dark) pixels 15 .…”
Section: Methodsmentioning
confidence: 99%
“…39; 74; 75 Lee et al measured Hounsfields Units (HU) and found a significant correlation between HU measurements and Goutallier grade in CT images (p<0.05). 44 Two other studies used different specialized software to quantitatively grade standard MRI sequences and reported excellent reliability (ICC 0.947 10 , ICC 0.997 43 ) and comparable results to newer Dixon MRI fat fractions and MR spectroscopy fat/water ratios. 10; 43 Both these computer-based techniques present viable alternatives to the Goutallier scale without the need for new imaging modalities, although accessibility of specialized computer programs may be an issue.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 95%